The Role of Purchase Intention as a Mediating Variable in the Relationship Between Promotion and Purchase Decisions - Elizabeth Tika Kristina Hartuti; Jaja Suteja; Juanim (Yayasan Putra Adi Dharma, 2026)
This study aims to analyze the influence of promotions on purchasing decisions with purchase interest as a mediating variable on Wuling brand car consumers in the Special Region of Yogyakarta (DIY). The research approach used is quantitative with an explanatory design. The sampling process uses accidental sampling, namely a sample determination technique based on respondents who are accidentally met by researchers and meet the criteria as research respondents with a sample size of 297 respondents and analyzed using covariance-based Structural Equation Modeling (SEM) with the help of LISREL 8.8 software. The analysis includes testing the measurement model (validity and reliability) and the structural model to test the direct effect of promotions on purchase interest and the mediating effect of purchase interest on the influence of promotions on purchasing decisions. The method used was an explanatory quantitative approach. Primary data were collected through a questionnaire with a Likert scale of 1–5. The analysis results showed that promotion had a direct, positive and significant effect on purchase intention, promotion also had a direct effect on purchase decisions, and purchase intention mediated the effect of promotion on purchase decisions. K